Características clínicas y microbiológicas de la infección del tracto urinario en gestantes atendidas en el Hospital II-2 Tarapoto, agosto 2015 – mayo 2016 - Ramirez García, Karen Vanessa (2016)
Objective: To determine the clinical and microbiological characteristics of urinary tract infection in pregnant women treated at Hospital II-2 Tarapoto. August 2015 - May 2016. Methodology: Descriptive, quantitative, cross-sectional study from a census type sample of 53 pregnant women with positive uroculture. The data collection was from data collection sheet. Results: Of the 53 pregnant women; 37.7% are 20-24 years old; 56.6% have secondary education; The civil status of 84.9% was cohabiting; The most frequent clinical form was asymptomatic bacteriuria with 49.1%; Lumbar pain with 26.4%, pelvic pain and dysuria with 24.5%, were the predominant symptoms; 54.7% were in the third trimester of gestational age; In 92.4% no associated complications were found; The most frequent isolated germ was Escherichia coli with 69.8%; It was found that Escherichia coli was sensitive to Cefotaxime, Ceftriaxone, Aztreonam. Conclusion: Urinary tract infection was more frequent in pregnant women of 20 and 24 years of age, with secondary education; The predominant clinical form: asymptomatic bacteriuria; The predominant symptoms were low back pain, pelvic pain and dysuria; Was more frequent in the third trimester of gestation; Most had no complications; E. coli was the most frequent etiological agent (69.8%); E. coli also had a higher frequency of sensitivity to Cefotaxime, Ceftriaxone, Aztreonam